Penerapan Alat Bantu Media Dinding Dalam Meningkatkan Akurasi Passing Bawah Bola Voli Peserta Ekstrakurikuler SMP Negeri 1 Ciniru - Aziz Ridwan Nur Muttaqin Aziz; Didi Muhtarom (Undiksha Press, 2025)
This study investigates the effect of wall media training on improving underhand passing accuracy in volleyball among extracurricular students at SMP Negeri 1 Ciniru. The problem arose from students’ difficulties in performing accurate passes due to limited training time and facilities. Wall media was chosen as a simple and accessible tool to support skill development.A quantitative method with a one-group pretest-posttest design was used. The sample consisted of 20 students, and data were collected through tests and observations. The results were analyzed using paired sample t-test.Findings showed a significant increase in passing accuracy, with posttest scores notably higher than pretest scores. Statistical analysis confirmed the improvement was significant (sig. < 0.05). This suggests that wall media training effectively enhances students’ underhand passing skills.In conclusion, wall media is an effective and practical training aid that can be used in schools with limited resources to improve basic volleyball techniques, especially underhand passing.